Comparative analysis of Student's live online learning readiness during the coronavirus (COVID-19) pandemic in the higher education sector. (July 2021) - Tang, Yuk Ming; Chen, Pen Chung; Law, Kris M.Y.; Wu, C.H.; Lau, Yui-yip; Guan, Jieqi; He, Dan; Ho, G.T.S.
Abstract: Amid the coronavirus outbreak, many countries are facing a dramatic situation in terms of the global economy and human social activities, including education. The shutdown of schools is affecting many students around the world, with face-to-face classes suspended. Many countries facing the disastrous situation imposed class suspension at an early stage of the coronavirus outbreak, and Asia was one of the earliest regions to implement live online learning. Despite previous research on online teaching and learning, students' readiness to participate in the real-time online learning implemented during the coronavirus outbreak is not yet well understood. This study explored several key factors in the research framework related to learning motivation, learning readiness and student's self-efficacy in participating in live online learning during the coronavirus outbreak, taking into account gender differences and differences among sub-degree (SD), undergraduate (UG) and postgraduate (PG) students. Technology readiness was used instead of conventional online/internet self-efficacy to determine students' live online learning readiness. The hypothetical model was validated using confirmatory factor analysis (CFA). The results revealed no statistically significant differences between males and females. On the other hand, the mean scores for PG students were higher than for UG and SD students based on the post hoc test. We argue that during the coronavirus outbreak, gender differences were reduced because students are forced to learn more initiatively. We also suggest that students studying at a higher education degree level may have higher expectations of their academic achievement and were significantly different in their online learning readiness. This study has important implications for educators in implementing live online learning, particularly for the design of teaching contexts for students from different educational levels. More virtual activities should be considered to enhance the motivation for students undertaking lower-level degrees, and encouragement of student-to-student interactions can be considered. Highlights: Explored key research questions in learning motivation, learning readiness, and student's efficacy in live online learning. Multi-group analysis and post hoc test to compare different genders, and sub-degree, degree, and postgraduate students. No significant differences between male and female students in live online learning readiness. Postgraduate students have significantly higher readiness in most aspects than undergraduate and sub-degree students. Educators should enhance the motivation of students from lower forms, and encourage their interactions and communication.